Metabolome profile and microbial community structure of Cenchrus fungigraminus silage under different moisture gradients - Hou, Xiaohan; Chu, Xiaohui; Yang, Yang; Xiao, Xue; Niu, Qiongmei; Shan, Guilian (Frontiers in Bioengineering and Biotechnology, 2025)
Due to its high biomass yield, Cenchrus fungigraminus is widely cultivated in Yunnan. Local herders often adjust the moisture content of fresh grass by sun-drying to improve its suitability for silage. However, the spatiotemporal dynamics of microbial communities and metabolites during its fermentation process remain unclear. In this study, fresh grass was subjected to natural sun-drying for 0, 12, 24, and 36 h, achieving moisture contents of approximately 88%, 77%, 66%, and 50%, respectively, before ensiling. We combined 16S rRNA high-throughput sequencing and LC–MS-based metabolomics to investigate changes in microbial diversity, community structure, and metabolic pathways under different moisture conditions. The results showed that, with prolonged sun exposure, the water-soluble carbohydrate (WSC) and ether extract (EE) of the raw material decreased, and the acid-insoluble fiber (ADF) also decreased; the richness and diversity of the microbial community in the low-moisture group (50%) after silage were significantly higher than those in the high-moisture group, accompanied by an increase in harmful bacteria such as Clostridium. In contrast, the abundance of lactic acid bacteria (LAB), including Lactobacillus and Weissella, showed a significant positive correlation with moisture content. Metabolomics analysis showed that essential amino acid-related pathways (aspartic acid and glutamic acid) were upregulated, while phenolic acid metabolism (protocatechuic acid and gallic acid) was downregulated, reflecting the differential regulation of fermentation products under different moisture conditions. In summary, although excessive sun-drying can optimize the fiber structure and palatability of raw materials, overly low moisture levels are unfavorable for the proliferation of probiotics and may compromise silage quality. Maintaining a higher moisture content (≥75%) for silage is more conducive to fermentation stability and nutritional value, providing a theoretical basis for optimizing the silage process of Cenchrus fungigraminus.